Anti-PCSK9 Monotherapy for Hypercholesterolemia: The MENDEL-2 Randomized, Controlled Phase III Clinical Trial of Evolocumab - KOREN, Michael J; LUNDQVIST, Pernille; BOLOGNESE, Michael; NEUTEL, Joel M; MONSALVO, Maria Laura; JINGYUAN YANG; KIM, Jae B; SCOTT, Rob; WASSERMAN, Scott M; BAYS, Harold (Journal of the American College of Cardiology, 2014)
The aim of this study was to compare biweekly and monthly evolocumab with placebo and oral ezetimibe in patients with hypercholesterolemia in a phase III trial. Evolocumab, a fully human monoclonal antibody against proprotein convertase subtilisin/kexin type 9 (PCSK9), significantly reduced LDL-C in phase II trials. Patients 18 to 80 years of age with fasting low-density lipoprotein cholesterol (LDL-C) ≥100 and <190 mg/dl and Framingham risk scores ≤10% were randomized (1:1:1:1:2:2) to oral placebo and subcutaneous (SC) placebo biweekly; oral placebo and SC placebo monthly; ezetimibe and SC placebo biweekly; ezetimibe and SC placebo monthly; oral placebo and evolocumab 140 mg biweekly; or oral placebo and evolocumab 420 mg monthly. A total of 614 patients were randomized and administered doses. Evolocumab treatment reduced LDL-C from baseline, on average, by 55% to 57% more than placebo and 38% to 40% more than ezetimibe (p < 0.001 for all comparisons). Evolocumab treatment also favorably altered other lipoprotein levels. Treatment-emergent adverse events (AEs), muscle-related AEs, and laboratory abnormalities were comparable across treatment groups. In the largest monotherapy trial using a PCSK9 inhibitor to date, evolocumab yielded significant LDL-C reductions compared with placebo or ezetimibe and was well tolerated in patients with hypercholesterolemia. (Monoclonal Antibody Against PCSK9 to Reduce Elevated LDL-C in Subjects Currently Not Receiving Drug Therapy for Easing Lipid Levels-2 [MENDEL-2]; NCT01763827).